Comprender lo virtual: conclusiones de un estudio evaluativo sobre reconstrucciones virtuales en los museos arqueológicos - Laia Pujol Tost (Virtual Archaeology Review)
This paper aims at presenting the conclusions of a middle-term research project undertaken in several European museums in order to obtain empirical data about the specific contribution of Virtual Reality for the dissemination of Archaeology, its integration in exhibitions and its perception and real use by audiences. The ultimate aim of this research project is to provide a theoretical and practical framework for the use of Virtual Reality in the Cultural Heritage field, in which professionals can find the basis of its specific usefulness, tools for its evaluation and, above all, guidelines for the design of future applications.